How Far Has Halal Travel Been Studied? - Aviyu Nekha; Dwi Ratna Kartikawati (SMART Insight, 2022)
The increasing growth of the Muslim population, followed by increasing religiosity, has led to a rising desire to travel with halal tourism. Not only are Muslim-majority countries aware of this, but non-Muslim countries are also interested in developing this market. This research aims to see the development of Halal Travel research worldwide published by journals with this theme. This study used a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme of Islamic halal travel originating from the Scopus database for 2011-2023. Then, the data is processed and analyzed using the VosViewer application to know the bibliometric map of the development of Halal Travel research worldwide. The study found six clusters related to Halal Travels: challenge in halal travel, halal travel in general, application Islamic value in halal travel, halal travel index, halal food in non-muslim country, and Intention and relationship muslim millennial for halal travel. The authors with the most published articles are Han H, Al-Ansi A, Rahman M. K, and Oktadiana H. The three keywords that appear the most are tourism, muslim tourist, and tourist. The author's affiliation is the university with the most publications dominated by Sejong University, UTM, and UPM. And countries with the most publications related to related studies are Malaysia, Indonesia, and South Korea.